India's informal economy : contractual labour in the formal manufacturing sector - Singh, Bir (Professor of economics) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The demand for economic inclusion has increasingly intensified, as manifested by the growing movements of farmers, workers, and social activists. Therefore, the question of adequate social representation of marginalized and underprivileged communities has to be made pivotal in the discourse of inclusion. This book investigates selected aspects of labour market informality in India. It examines the key factors that have expedited labour informality- contractualisation - in the manufacturing sector since the early 1990s. It analyses the features of informality and inclusion from the perspective of not just class but also the caste hierarchy in Indian society, thus offering readers an exhaustive overview of economic inclusion following the economic reforms and providing fresh insights into labour market informality through the lens of the social divisions in Indian society. Developed on a wide canvas of multiple processes, policies and factors that have contributed to this phenomenon, the book offers an elaborate analysis of contractualisation within the industry from the perspectives of labour legislation and the labour market. In addition, it contextualizes the issue of job informality for the post economic reforms era, from 1991 onwards. It examines the impact of the policies of economic reform on contractualisation across industries and states. Further, the book discusses the dynamics of the labour market reforms in India, given that there is a higher incidence of labour informality in India. It also highlights how the policy quest for inclusive growth has remained unfulfilled. This book will be a useful guide for advanced students, academic researchers, scholars and policy makers that are engaged with the issue of informal sector employment"--
Keywords: Labor market -- India; Informal sector (Economics) -- India; Manufacturing industries -- India; Under-the-table employment -- India; BUSINESS & ECONOMICS / Labor; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Economic Conditions